Students’ Understanding on Simple Past Tense through VOA Learning English YouTube Channel - Lailatul Mahmudah; Lidiyatul Izzah (English Language in Focus (ELIF), 2019)
The objective of the study is to find out the effect of VOA Learning English YouTube Channel on students’ simple past tense. This study was conducted at 8th grade students of SMP Pustek Serpong in academic year 2017/2018. The researcher used quantitative analysis with a quasi-experimental design. As the sample, the researcher uses one class with total number of 37 students. By using t-test, the finding showed that tcalculation (7.89) was higher than ttable (2.026) at a significant level of 5%. It indicates that VOA Learning English YouTube Channel gives the positive significant result in improving students’ simple past tense.